Confidentiality and public interest disclosure: A framework to evaluate UK healthcare professional regulatory guidance. (March 2022) - Snelling, Paul; Quick, Oliver
Confidentiality and disclosure of information in the public interest present difficult dilemmas for healthcare practitioners and call for clear legal and regulatory guidance. The common law duty of confidence, and established exceptions to it, are shaped by medical practice and detailed guidance produced by the General Medical Council. Guidance issued by other healthcare regulators in a highly fragmented environment is at best unclear and at worst inaccurate. This article assembles and justifies a framework of evaluation against which regulators' guidance can be assessed, focussing on the specific issue of when the duty of confidentiality can be set aside in the public interest. Comparison of statutory regulators' guidance reveals wide variation which creates uncertainty for practitioners confused by inconsistency between guidance documents. The results of this analysis raise questions about the relationship between common law and regulatory guidance, in particular, whether it is appropriate to recognise different standards for different healthcare professions. This article argues that there is an opportunity to correct this anomaly and ensure appropriate consistency as part of a wider review of healthcare professional regulation.